Study of anodic oxide films formed on solid-state sintered SiC-ceramic at high anodic potentials. Issue 11 (1st June 2021) - Schneider, M.; Šimůnková, L.; Michaelis, A.; Noeske, M.; Aniol, J.; Thiel, K.
Abstract: The present work studies the formation, chemical composition, and structure of an oxide layer formed on the technical solid-state sintered ceramic (EKasic®D) in a strong alkaline solution (1 M NaOH at pH 14) at high anodic potentials (30 V vs. 3 M Ag/AgCl). The observed formation of oxide films on SiC in alkaline solution is in contradiction to the thermodynamic laws (Pourbaix-diagram). The film thickness was determined by SEM/EDX measurements using the specific thin film analysis tool "AZtec" (Oxford Instruments) as well as the transmission electron microscopy. The thickness of the oxide film formed at 30 V amounts to 30 nm that corresponds with a field strength of E = 10 MV cm −1, which corresponds with the formation according to the high-field mechanism. The chemical composition was studied by EDX-analysis in a transmission electron microscope as well as by X-ray photoelectron spectroscopy (XPS). The oxide layer is completely amorphous and consists of non-stoichiometric SiOx and SiOx Cy . The layer is assumed as graded with a higher amount of SiOx in the outermost regions and an increased amount of SiOx Cy in the inner region of the passive layer. Additionally, the passive layer is doped by a small amount of aluminum originating from a sinter additive used in the manufacture of the SiC ceramic and completely incorporated into the SiC grains.